Analysing drivers of knowledge leakage in collaborative agreements: A magnetic processing case firm - Samuel Foli; Susanne Durst (Journal of Risk and Financial Management, 2022)
Due to the embeddedness of organisations in networks, collaborations, and business relationships, knowledge leakage has become a common concern. In this regard, this paper aims to investigate drivers of knowledge leakage in collaborative agreements using an integrated ISM-MICMAC model. Based on insights from employees including the CEO of a magnetic processing firm, we validate the proposed model. The findings of our study reveal nine key drivers that influence knowledge leakage in collaborative agreements. In terms of level of influence, incomplete contract is the most influential driver, followed by sub-contracting activities. Last, the nine drivers are classified into two main clusters: independency cluster-weak dependence power with high driving power-and linkage cluster-strong dependence and driving power.
Keywords: 650; case study; collaborative agreements; driver; interpretive structural model (ISM); knowledge leakage; MICMAC analysis; small firm